Creating Shared Valua As Profit and Social Welfare Growth Solution - Hardyanto Rivai; Gagaring Pagalung (The Indonesian Journal of Accounting Research, 2014)
Abstract:The purposes of this paper are to measure the means different of profit and social welfare indicators in creating shared value and corporate social responsibility implementation and to explore the relationship between return on asset and direct and indirect energy consumption, direct and indirect greenhouse gases, and fatalities of employees in creating shared value implementation. The data involving 30 corporates listed on world securities exchange, from 2003 to 2010 is conduct. The data analyses are compare-means independent sample t-test and linear multiplier regression. The results were found (i) the means of profit and social welfare indicators in creating shared value and corporate social responsibility implementation are significantly different; (ii) negative relationship between return on asset and direct and indirect energy consumption, direct and indirect greenhouse gases, and fatalities of employees in creating shared value implementation.Abstrak: Tujuan makalah ini adalah untuk mengukur sarana yang berbeda dari indikator laba dan kesejahteraan sosial dalam menciptakan nilai bersama dan pelaksanaan tanggung jawab sosial perusahaan dan untuk mengeksplorasi hubungan antara laba atas aset dan konsumsi energi langsung dan tidak langsung, gas rumah kaca langsung dan tidak langsung, dan korban jiwa karyawan dalam menciptakan implementasi nilai bersama. Data yang melibatkan 30 perusahaan yang terdaftar di bursa efek dunia, dari 2003 hingga 2010 adalah perilaku. Analisis data adalah membandingkan-berarti uji t sampel independen dan regresi linier berganda. Hasilnya ditemukan (i) sarana profit dan indikator kesejahteraan sosial dalam menciptakan nilai bersama dan pelaksanaan tanggung jawab sosial perusahaan secara signifikan berbeda; (ii) hubungan negatif antara laba atas aset dan konsumsi energi langsung dan tidak langsung, gas rumah kaca langsung dan tidak langsung, dan kematian karyawan dalam menciptakan implementasi nilai bersama.